Manajemen Soft Skill: Bentuk Upaya Peningkatan Kemampuan Siswa di Madrasah - M Thoyyib (Institut Agama Islam Al-Hikmah Tuban, 2022)
Soft skills are attributes that enable a person to engage in meaningful interactions with others. Since most jobs require teamwork, it's important to have soft skills to improve employability and achieve your dream job. Soft skills will help increase productivity in your career, build professional relationships and thrive in the world of work. Therefore, since at school, students need to be supported in order to be able to improve their soft skills. So it is necessary to have good soft skill management from schools to support this. The management in question includes planning, organizing, actuating and controlling. Considering the large number of madrasas in Indonesia which will give birth to many graduates, the management of soft skills in madrasas needs special attention.